Studi Kualitas Air Tanah Berdasarkan Sifat Fisik dan Kimia Menggunakan Analisis Hidrogeologi dan Hidrokimia di Jakarta Barat - albar karismawan; Dyah Nindita Sahdarani; Mochammad Prahastomi; Tantowi Eko Prayogi (Jurnal Inovasi Pendidikan dan Sains, 2021)
The study of Groundwater in West Jakarta is to determine the quality of groundwater that is commonly used by residents for their daily needs such as drinking, clean up and etc. This study is important because the water consumed by residents does not necessarily meet standard of raw water quality for drinking set by the government through Permenkes No. 492 of 2010, through physical and chemical parameters. The research focuses on examining free aquifers in densely populated housing by using hydrogeological and hydrochemistry analysis. This research aims to condition groundwater by hydrogeology and hydrochemistry method and also mapping water quality. Hydrogeological analysis is used to map ground water level based on groundwater depth measurements measured in community wells with units of meters below ground level (mgmt) and meters below sea level (m.asl).Hydrochemical data uses two data, namely primary and secondary data. Primary data is data taken by the author in the field in 2021 by focusing on free aquifer groundwater wells taken in densely populated housing. Secondary data is data taken by BKAT in 2018-2020 by focusing on groundwater wells for public spaces such as gas stations, parks, and houses of worship. So that the hydro chemical analysis produces two types of maps, the first map is groundwater quality of free aquifers in public spaces through BKAT data, and a map of groundwater quality in densely populated housing in 2021. The results of the hydrogeological research are making a map of the free aquifer zone, and a map of the average change in groundwater level in West Jakarta. While the hydro chemical analysis was carried out to see the conditions of salinity, type of water, the level of seawater intrusion and the total dissolved solids in the study area.Based on measurements made by the author in March 2021, the deepest water depth is in Semanam Village with a depth of 9.3 mgmt., and the shallowest is in Rawa Buaya village with a depth of 0.2 mbmt. Meanwhile, based on the author’s measurements, groundwater quality are chagrin. Roa Melaka Village has smelly water, also high in Chloride, Sodium, and Natrium. Duri Kepa and Jelambar Village have high iron pollution, through measurement have 0,4 mg/l and 1,65 mg/l.